Learning Commons: Sebuah Strategi Layanan Perpustakaan - Anisa Sri Restanti (LIBRARIA : Jurnal Ilmu Perpustakaan dan Informasi, 2017)
The development of information technology brings various changes in allaspects of life. In today’s era, the diversity of information sources with theease of access in search engines integrated into the internet becomes commonplace.The behavior of the user begins to change with the birth of the netgeneration. The library seems to be demanded by technological developmentsthat are so rapidly innovating in improving the quality of its services. Learningcommons is a concept that can be applied in libraries to always be closeto the user and not left them. This writing discusses various things relatedto learning commons. This study was conducted to determine the benefitsof learning commons and to know how the challenges and application oflearning commons in the library. This study uses literature study method.The results of the study show that the implementation of learning commonsin the library can strengthen the library’s brand image and improve thequality of library services. Based on these results can be concluded that theapplication of learning commons can be used as a service strategy in thelibrary and can defend the existence of libraries in the digital era.